Primary immune thrombocytopenia in children - Książek, Agnieszka; Szczepański, Tomasz (Pediatria Polska - Polish Journal of Paediatrics, 2021)
Primary immune thrombocytopenia (ITP) is usually a benign and self-limiting disease in children. Due to the complex pathogenesis involving different immunological processes, its course may be unpredictable. The goal of therapy is to prevent severe, dangerous bleeding, especially intracranial bleeding. In addition to purpura, i.e. ecchymoses and bruises on the skin, mucosal bleeding may occur, e.g. from nose, gums, excessive menstrual bleeding, as well as severe bleeding from the gastrointestinal or urinary tract. First-line therapy relies on glucocorticoids (GKS) or intravenous immunoglobulins (IVIgG). The next stage of treatment is the inclusion of other immunosuppressive drugs or cytotoxic drugs. The introduction of thrombopoietin receptor agonists (TPO-RAs) for the treatment of this disease has been the biggest progress over the past 20 years. TPO-RAs are treatment of choice for chronic ITP. Splenectomy is now reserved only for children with chronic ITP resistant to thrombopoietin receptor agonists..